(untitled) (The Review of Diabetic Studies, 2024)
Background: Prepatellar bursitis is an inflammatory condition affecting the superficial bursa anterior to the patella, commonly caused by repetitive kneeling, direct trauma, infection, or systemic inflammatory diseases. Its superficial location predisposes it to mechanical irritation and septic complications, making timely diagnosis essential for preventing morbidity. Aim: This study aims to integrate clinical, imaging, therapeutic, pharmacological, nursing, and health‑information perspectives to provide a comprehensive, evidence‑based approach to the evaluation and management of prepatellar bursitis. Methods: A multidisciplinary review was conducted, examining anatomical characteristics, etiological factors, epidemiology, pathophysiology, clinical presentation, diagnostic tools, and treatment strategies. The study synthesizes current literature, imaging modalities such as ultrasound and MRI, fluid aspiration analysis, and conservative to advanced therapeutic interventions. Results: Prepatellar bursitis is most frequently associated with mechanical trauma and occupational kneeling. Infection accounts for up to one‑third of clinically presenting cases. Ultrasound proved valuable in differentiating bursitis from cellulitis, while aspiration remained the diagnostic gold standard in suspected septic cases. Most nonseptic cases responded to conservative management, whereas septic bursitis required antibiotics, repeated aspiration, and sometimes surgical drainage or bursectomy. Chronic or recurrent cases benefited from corticosteroid injection, sclerotherapy, or minimally invasive endoscopic excision. Conclusion: An interdisciplinary management strategy significantly improves diagnostic accuracy, treatment outcomes, and prevention of complications. Early recognition, proper differentiation between septic and nonseptic etiologies, and individualized care optimize prognosis and minimize recurrence.